Spontaneous Pneumomediastinum, Pneumoperitoneum, and Subcutaneous Emphysema beyond the Inguinal Ligament Secondary to Inversion Maneuvers - Keegan Plowman; David Lindner; Jose Ruben Valle-Giler (Case Reports in Pulmonology)
Pneumomediastinum is free air within the mediastinal cavity which can spread along tissue planes leading to the accumulation of large amounts of subcutaneous emphysema. Patient is a 21-year-old male with a history of autism spectrum disorder and rhabdomyolysis who presented with diffuse “popping under the skin” and was found to have crepitus extending from his neck to his bilateral ankles. He exercises frequently and performs chin-up pullovers and will often hold his breath during this movements. He uses an inversion table but denies any valsalva maneuvers or straining while inverted. Radiological imaging demonstrated pneumomediastinum, pneumoperitoneum, and diffuse subcutaneous emphysema extending into the pelvis. Diagnosis requires a combination of history, physical exam findings, and imaging findings. Patients with spontaneous pneumomediastinum typically experience self-limited disease, and efforts should be made to minimize low yield invasive testing. Most patients can be treated on an outpatient basis after monitoring and education about potential complications.